Reviewing Gertrudis Gómez de Avellaneda from the history of women (La Aljaba. Segunda Época. Revista de Estudios de la Mujer, 2019)
This study carries out a revision of the figure of the Hispanic-Cuban writer Gertrudis Gómez de Avellaneda (1814-1873), from the methodological approaches corresponding to the History of Women and Feminism from which this author has been analysed in the last decades. It starts from the hypothesis of the importance of analyzing the written production of this writer, in order to know the woman behind its authorship. It tries to penetrate her biography and her work from key texts for the understanding of herself; using for it the autobiography and the correspondence that the writer wrote destined to Ignacio de Cepeda.
Keywords: Gertrudis Gómez de Avellaneda; autobiography; collection of letters; biography; literary work; History of Women